2012
DOI: 10.1143/apex.5.023003
|View full text |Cite
|
Sign up to set email alerts
|

Spin Accumulation in Nondegenerate and Heavily Doped p-Type Germanium

Abstract: Spin accumulation induced in p-type germanium from Fe/MgO tunnel contacts is studied as a function of hole concentration p (10^16 - 10^19 cm-3). For all p, the contacts are free of rectification and Schottky barrier, guaranteeing spin injection into the Ge and preventing spin accumulation enhancement by two-step tunneling via interface states. The observed spin accumulation is smallest for nondegenerate doping (p ~ 10^16 cm-3) and increases for heavily doped Ge. This trend is opposite to what is expected from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 22 publications
3
50
0
Order By: Relevance
“…The spin RA product also displays an exponential variation with thickness of the tunnel oxide, and a power law is revealed when the spin RA product is plotted against tunnel resistance [see Figs [20,21], we also find that R tun and the spin RA product vary exponentially with MgO thickness [see Fig. 3(c)], although the data set is too limited to extract an accurate value for the scaling exponent.…”
Section: Scaling With Tunnel Barrier Thicknessmentioning
confidence: 73%
See 1 more Smart Citation
“…The spin RA product also displays an exponential variation with thickness of the tunnel oxide, and a power law is revealed when the spin RA product is plotted against tunnel resistance [see Figs [20,21], we also find that R tun and the spin RA product vary exponentially with MgO thickness [see Fig. 3(c)], although the data set is too limited to extract an accurate value for the scaling exponent.…”
Section: Scaling With Tunnel Barrier Thicknessmentioning
confidence: 73%
“…Note that for the devices with an Al 2 O 3 tunnel barrier, the line width depends slightly on the oxidation time. The spin lifetime for devices with MgO/Fe contacts is smaller than with Al 2 O 3 /Ni 80 Fe 20 contacts. This can be attributed to broadening of the Hanle curve by inhomogeneous magnetostatic fields, which is more pronounced for Fe owing to its larger magnetization [34].…”
Section: E Two-step Tunneling Via Localized States Within the Tunnelmentioning
confidence: 93%
“…This is about 3 orders of magnitude smaller that the experimental values. Interestingly, several research groups using three-terminal Hanle measurements have also reported such large values in Si [1][2][3][4][5][6][7]30 , Ge 11,12,[14][15][16][17] , and GaAs 29 , no matter what type of tunnel barrier was used. As it was recently discussed 37,38 , the origin of the discrepancies is not clear yet.…”
Section: Spin Accumulation In P-type Si Using Fe/mgo Contactsmentioning
confidence: 99%
“…Hence, one can expect that MgO is also an effective tunnel barrier for Si-based spintronics devices if a thin MgO(001) layer can be epitaxially grown on Si. Whereas epitaxial growth of FM/MgO(001) for spin injection on Ge [11][12][13][14][15][16][17] and GaAs [18][19][20] has been intensively studied, the way towards epitaxial growth of MgO on Si is still not well established. Therefore, it is important to clarify the growth techniques and conditions for achieving epitaxial FM/MgO(001) layers on Si 4,7,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] as well as into Ge through MgO. [26][27][28][29][30][31][32][33][34] Among the latest experiments, the transformation of a spin-polarized electron current into left-or righthanded circularly polarized light in a spin light-emitting diode (spin LED) integrating a III-V semiconductor heterostructure 8,11,[13][14][15][16][17]19,23,34,35 is one of the most striking physical phenomena. The electric dipolar selection rules involved in a quantum well 36 (QW) embedded in a spin LED during electron-hole recombination require spin injection with an out-of-plane magnetization.…”
Section: Introductionmentioning
confidence: 99%